Seychelles : Staff Report for the Eight Review Under the Extended Arrangement. (IMF Staff Country Reports; Country Report ;, 2014)
On December 19, 2013, the Executive Board of the IMF completed the eighth and final review under the Extended Fund Facility (EFF) for Seychelles. The completion of the review enables a disbursement of SDR 3.3 million, which will bring total disbursements under the arrangement to SDR 26.4 million. Strong policies have fostered economic growth, brightening Seychelles' near-term outlook. With the completion of this review, the EFF arrangement comes to an end. The program's key objective of placing the economy firmly on the path to external and fiscal sustainability has been achieved, based on the successful implementation of the debt restructuring, robust fiscal consolidation, and the resumption of growth.